The Trump foreign policy record and the concept of transformational change. Issue 1 (1st January 2020) - Ashbee, Edward; Hurst, Steven
ABSTRACT: While there has been debate about the extent to which US foreign policy has been transformed since President Trump first took office in 2017, the concept of transformational policy change has not been defined with any degree of precision. The purpose of this article is, primarily, to establish such a definition. It does this by drawing upon a number of the literatures that address domestic policy processes, in particular the work of Karl Polanyi, to suggest that transformational change rests upon paradigmatic shifts, the reconfiguration of interests, large scale institutional re-ordering and changed logics. Application of the definition to the Trump foreign policy leads us to conclude that while the Trump foreign policy owes much to the militant internationalism of the Bush years its understanding of nations and "globalism" and abandonment of a defining moral purpose represent, although incipient, partial and variegated, the beginnings of transformational change.